2014
DOI: 10.1177/0284185113499752
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the cervical spinal cord in healthy adult population: normative values and measurement reproducibility at 3T MRI

Abstract: Both ROI- and FT-based measurements are applicable methods yielding reproducible results for cervical spinal cord DTI metrics. Normative values for both measurement methods are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
5
26
1
Order By: Relevance
“…5,8 It has also been reported that in adult cervical SC DTI, there is good intra-and interobserver variability. 16 In our current study, we have shown that within the cervical and thoracic SC, DTI values showed moderate-to-strong repeatability. These findings add to the existing evidence that DTI values for the normal SC are repeatable.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…5,8 It has also been reported that in adult cervical SC DTI, there is good intra-and interobserver variability. 16 In our current study, we have shown that within the cervical and thoracic SC, DTI values showed moderate-to-strong repeatability. These findings add to the existing evidence that DTI values for the normal SC are repeatable.…”
Section: Discussionsupporting
confidence: 52%
“…The coefficient of variation showed that the variability of the DTI parameters was very good for both age groups and similar to other reports of DTI measurement variability. 16 Overall, FA showed the least variability (6 -11 years, 16.66%; 12-16 years, 17.24%). Table 3 shows the intraclass correlation coefficient and 95% CIs for test-retest repeatability of DTI values for the cervical and thoracic SC.…”
Section: Coefficient Of Variationmentioning
confidence: 92%
“…[12][13][14][17][18][19] We observed interimager variability in the ADC values of gray and white matter and a wide range of ADC values of gray matter that was probably attributable to tissue-specific characteristics. One histological difference between gray and white matter is capillary perfusion, as suggested by the intravoxel incoherent motion (IVIM) theory.…”
Section: ¹6mentioning
confidence: 74%
“…Although these data are compatible with our results, other studies concluded that the ADC values at 1.5T and 3T are almost identical. 14,17 Interimager variability must be considered on an imager-by-imager basis.…”
Section: ¹6mentioning
confidence: 99%
See 1 more Smart Citation